Daptomycin selects for genetic and phenotypic adaptations leading to antibiotic tolerance in MRSA. (27th April 2018) - Berti, Andrew D; Shukla, Neehal; Rottier, Aaron D; McCrone, J Sue; Turner, Hannah M; Monk, Ian R; Baines, Sarah L; Howden, Benjamin P; Proctor, Richard A; Rose, Warren E
Abstract: Objectives: Daptomycin non-susceptibility in Staphylococcus aureus can emerge via the accumulation of single or multiple mutations, each resulting in a slight increase in the daptomycin MIC. The daptomycin-non-susceptible phenotype may include other features such as daptomycin tolerance. This study identifies S. aureus genomic regions that frequently develop mutations following prolonged daptomycin exposure but have not been previously associated with daptomycin non-susceptibility. Methods: Sequence variations in the same eight loci independently observed following 28 day parallel serial passages of S. aureus J01 in daptomycin were introduced in isolation into S. aureus J01. MICs were determined by microbroth dilution. Daptomycin killing and tolerance were determined by kill curve analysis. Results: Single mutations in snoF, hmp1, sspA, rimP, hepT, rsh, map1 and amaP had only a modest impact on the daptomycin MIC (≤2-fold). In contrast, individual mutation in several of these regions resulted in pronounced changes to daptomycin tolerance. Conclusions: This study demonstrates that less characterized mutations in S. aureus following daptomycin exposure do not result in significant daptomycin susceptibility changes, but rather allow for enhanced survival characteristics during treatment. This sheds new light on genetic adaptations that may play a role in persistent infection. Further studies are needed to elucidate the prevalence of these mutations in clinical isolates.